The hemodynamic performance of balloon-expandable aortic bioprostheses in the elderly: a comparison between rapid deployment and transcatheter implantation - Fortunato Iacovelli; Paolo Desario; Alessandro Cafaro; Antonio Pignatelli; Rossella Alemanni; Rosamaria Montesanti; Alessandro Santo Bortone; Emanuela De Cillis; Micaela De Palo; Luca Bardi; Gian Luca Martinelli; Tullio Tesorio; et al. (Hellenic Journal of Cardiology, 2022)
Background: Surgical aortic valve replacement with a rapid deployment valve (RDV) is a relatively recent treatment option. The aim of this study was to compare the hemodynamic performance of balloon-expandable (BE)-RDVs and BE-transcatheter heart valves (THVs) in a high surgical risk and frail-elderly population. Methods: BE-THVs and BE-RDVs were implanted in 138 and 47 patients, respectively, all older than 75 years and with a Canadian Study of Health and Aging category of 5 or above. Echocardiographic assessment was performed at discharge and six months later. Results: At discharge, transprosthetic pressure gradients and indexed effective orifice area (iEOA) were similar in both cohorts. At six-month follow-up, BE-RDVs showed lower peak (14.69 vs. 20.86 mmHg; p < 0.001) and mean (7.82 vs. 11.83 mmHg; p < 0.001) gradients, and larger iEOA (1.05 vs. 0.84 cm2/m2; p < 0.001). Similar findings were also shown considering only small-sized valves. Moderate-to-severe paravalvular leakage was more prevalent in BE-THVs at discharge (14.49 vs. 0.00%; p = 0.032) and, considering exclusively small prostheses, at six months too (57.69 vs. 15.00%; p = 0.014). Nevertheless, BE-THVs determined amelioration in left ventricular ejection fraction (53.79 vs. 60.14%; p < 0.001), pulmonary artery systolic pressure (35.81 vs. 33.15 mmHg; p = 0.042), and tricuspid regurgitation severity (40.58 vs. 19.57%; p = 0.031), from discharge to mid-term follow-up. Conclusions: BE-RDVs showed better hemodynamic performance, especially when implanted in small annuli. Despite their worse baseline conditions, transcatheter patients still exhibited a greater improvement of their echocardiographic profile at mid-term follow-up.